2005
DOI: 10.1149/1.1861037
|View full text |Cite
|
Sign up to set email alerts
|

High Optical Quality Nanoporous GaN Prepared by Photoelectrochemical Etching

Abstract: Abstract--Nanoporous GaN films are prepared by UV assisted electrochemical etching using HF solution as an electrolyte. To assess the optical quality and morphology of these nanoporous films, micro-photoluminescence (PL), micro-Raman scattering, scanning electron microscopy (SEM), and atomic force microscopy (AFM) techniques have been employed. SEM and AFM measurements revealed an average pore size of about 85-90 nm with a transverse dimension of 70-75 nm. As compared to the as-grown GaN film, the porous layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 27 publications
(11 reference statements)
4
50
0
Order By: Relevance
“…Similar to the nanoporous GaN film obtained by photoelectrochemical etching (PEC) [23], such a red-shifted emission is due to partial relaxation of compressive stress in the etched nonpolar GaN. The surface covered with etch-pits maybe helps to accommodate the lattice mismatch induced strain.…”
Section: Resultsmentioning
confidence: 59%
“…Similar to the nanoporous GaN film obtained by photoelectrochemical etching (PEC) [23], such a red-shifted emission is due to partial relaxation of compressive stress in the etched nonpolar GaN. The surface covered with etch-pits maybe helps to accommodate the lattice mismatch induced strain.…”
Section: Resultsmentioning
confidence: 59%
“…to the relaxation of the compressive stress in the porous samples, which can be further confirmed by Raman scattering [17] and X-ray diffraction [18]. On the other hand, the PL intensity for the etched samples are found to be increased, which could mainly be attributed to the enhancement of the photon extraction efficiency due to more photons scattering from the sidewalls of the NP GaN [19].…”
Section: Characterization Of Np Gan Thin Filmsmentioning
confidence: 64%
“…However, it will not be a dominant effect in the observed results on the GaN porous structures, where the surface defect would be preferentially etched due to weak atomic bonding and high chemical activity. Another study [10] showed that the redshift of about 10 meV was caused by the stress relaxation in the GaN porous structures. However, the redshift observed in this study was as large as 100 meV, which could not be explained by the effect of the stress relaxation.…”
Section: Possible Model Of Large Photocurrents and Redshift Of Photoamentioning
confidence: 99%